The Aqil Baligh in Islam and Lawrence Kohlberg's Theory of Moral Development: A Comparative Study - Arham Muhammad Robbani; Yudhi Munadi (Yayasan Darusssalam Bengkulu, 2026)
This study aims to analyze the concept of aqil baligh in Islam and examine its relevance to Lawrence Kohlberg’s theory of moral development. The study is motivated by the gap between adolescents’ biological maturity and their moral reasoning maturity amidst contemporary moral challenges. This study employs a qualitative approach using a literature review method. Data were obtained from literature on fiqh, Islamic education, and modern moral development theory, and were analyzed using content analysis techniques. The results indicate that aqil baligh in Islam marks the beginning of the taklif phase, encompassing biological, rational, and spiritual dimensions. Meanwhile, Kohlberg’s theory explains that moral development proceeds in stages through a structure of moral reasoning. Both share a common focus on the role of reason but differ in their sources of moral legitimacy. Islam is based on revelation, whereas Kohlberg’s theory is grounded in human rationality and the principle of universal justice. This study concludes that understanding adolescent moral maturity requires an integrative approach that combines biological, cognitive, and spiritual dimensions.